The Distal and Local Volcanic Ash in the Late Pleistocene Sediments of the Termination I Interval at the Reykjanes Ridge, North Atlantic, Based on the Study of the Core AMK-340 - Alexander Matul; Irina F. Gablina; Tatyana A. Khusid; Natalya V. Libina; Antonina I. Mikhailova (Geosciences, 2019)
We made the geochemical analysis of the volcanic material from the sediment core AMK-340 (the Russian research vessel “Akademik Mstislav Keldysh” station 340), the central zone of the Reykjanes Ridge. Two ash-bearing sediment units within the interval of the Termination I can be detected. They correlate with the Ash Zone I in the North Atlantic Late Quaternary sediments having an age of 12,170−12,840 years within the Younger Dryas cold chronozone and 13,600−14,540 years within the Bølling−Allerød warm chronozone. The ash of the Younger Dryas unit is presented mostly by the mafic and persilicic material originated from the Icelandic volcanoes. One sediment sample from this unit contained Vedde Ash material. The ash of the Bølling−Allerød unit is presented mostly by the mafic shards which are related to the basalts of the rift zone on the Reykjanes Ridge, having presumably local origin. Possible detection of Vedde Ash could help to specify the timing of the previously reconstructed paleoceanographic changes for the Termination I in the point of the study: significant warming in the area might have occurred as early as 300 years before the end of the conventional Younger Dryas cold chronozone.